2009
DOI: 10.1088/0957-4484/21/3/035201
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale control of the network morphology of high efficiency polymer fullerene solar cells by the use of high material concentration in the liquid phase

Abstract: Despite the constant improvement of their power conversion efficiencies, organic solar cells based on an interpenetrating network of a conjugated polymer as donor and fullerene derivatives as acceptor materials still need to be improved for commercial use. In this context, we present a study on the optimization of solar cells based on poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl C61 butyric acid methyl ester (PCBM) by varying a specific cell parameter, namely the concentration of the active layer components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 22 publications
3
41
0
Order By: Relevance
“…The solid content of ink drives the viscosity and it has been demonstrated that a varying concentration greatly affects the PV performance. [ 54 ] Also, most PV inks can show gelation behaviors due to liquid-state aggregation during the ageing of solutions stored at room temperature. [ 55 ] As a consequence, the stirring, storage, and heating temperature of P3HT:PCBM before coating layers are critical; yet, rare are the authors accurately mentioning the ink history.…”
mentioning
confidence: 99%
“…The solid content of ink drives the viscosity and it has been demonstrated that a varying concentration greatly affects the PV performance. [ 54 ] Also, most PV inks can show gelation behaviors due to liquid-state aggregation during the ageing of solutions stored at room temperature. [ 55 ] As a consequence, the stirring, storage, and heating temperature of P3HT:PCBM before coating layers are critical; yet, rare are the authors accurately mentioning the ink history.…”
mentioning
confidence: 99%
“…The value of HOMO and LUMO may vary from ~ 4.92 to 5.20 and 2.66 to 3.40, respectively depending upon the nature of the thin film [1,24]. The energy level diagram of the device shows that ITO and Al are taken as anode and cathode where the energy gap for electron is ~ 0.80 eV (between Aluminium and LUMO of CoPc) and for hole, the energy gap is ~ 0.10 eV (between ITO and HOMO of CoPc) [25][26][27][28][29]. There is very less probability for injection of electron in the device due to this large energy gap.…”
Section: Resultsmentioning
confidence: 99%
“…The solvent annealing process, which leads to phase segregation after deposition of the solution under a saturated solvent atmosphere, affects the spinodal decomposition in the liquid phase and can yield efficient devices 60. Consequently, it may be possible to control the phase separation kinetics by changing the material's concentration 61, 62. It was shown by the Plastic Optoelectronics Group (Limoges University, France) that, at very high material concentrations in the liquid phase, the free space limitation between moieties will slow down molecular rearrangement giving a smaller segregated domain size 62.…”
Section: Polymer Solar Cells a Brief Reviewmentioning
confidence: 99%
“…Consequently, it may be possible to control the phase separation kinetics by changing the material's concentration 61, 62. It was shown by the Plastic Optoelectronics Group (Limoges University, France) that, at very high material concentrations in the liquid phase, the free space limitation between moieties will slow down molecular rearrangement giving a smaller segregated domain size 62. The high efficiency solar cells thus obtained have been observed by ultrahigh vacuum near field investigation (Kelvin probe force microscopy), performed by the CEA (Grenoble, France), and have given the best resolved surface potential images of a P3HT‐PCBM active layer blend to date,63 with an IPN domain size around 15 nm.…”
Section: Polymer Solar Cells a Brief Reviewmentioning
confidence: 99%